Raman Slow Light in Distributed Raman Fiber Sensors - Dapeng Wang; Ning Li; Aimei Yan; Yingxin Xie; Fengyu Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Distributed Raman sensor offers a number of advantages to the implementation of smart grid, which is aimed to improve reliability and energy efficiency as compared with traditional power grid. However, the fantastic properities of slow light are rarely considered in the former studies on the Raman sensor systems. In this paper, the effects of Raman slow-light on room-temperature single-mode optical fiber sensors are examined by extracting the Raman pulse-delay terms from extended nonlinear Schrodinger equation (NLSE). Numerical study shows that pulse parameters such as pulse position, frequency chirp, and envelope distortion may be greatly affected by slow light. Two important points of pump power are show clearly keeping the Raman pulse zero walk-off or chirp free, respectively. We demonstrate a method based on pump power adjustment for compensating the slow light induced impairment. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2472